2019
DOI: 10.1016/j.ejmech.2019.111600
|View full text |Cite
|
Sign up to set email alerts
|

Carbonic anhydrase inhibitors based on sorafenib scaffold: Design, synthesis, crystallographic investigation and effects on primary breast cancer cells

Abstract: This is a pre-copyedited, author-produced version of an article accepted for publication in European Journal of Medicinal Chemistry following peer review. The version of record "Carbonic anhydrase inhibitors based on sorafenib scaffold: Design, synthesis, crystallographic investigation and effects on primary breast cancer cells"

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 69 publications
0
23
0
Order By: Relevance
“…8. General Procedure for the Synthesis of compound [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. A solution of 5a-b (0.2 g, 1.0 eq) in dry MeOH was treated with Et 3 N (1 eq) then the reaction mixture was cooled to 0 • C and benzaldehyde 6-15 (1 eq) was added.…”
Section: Chemistrymentioning
confidence: 99%
See 2 more Smart Citations
“…8. General Procedure for the Synthesis of compound [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. A solution of 5a-b (0.2 g, 1.0 eq) in dry MeOH was treated with Et 3 N (1 eq) then the reaction mixture was cooled to 0 • C and benzaldehyde 6-15 (1 eq) was added.…”
Section: Chemistrymentioning
confidence: 99%
“…An important structural consideration is the role of the linker connecting the tail and the warhead sections within CAI molecules in order to make use of the tail strategy. The ureidic moiety was demonstrated to be particularly suitable as it allows the entire molecule to assume the best conformation when allocated within the enzyme cavity and at the same time to contribute to the stabilization of the enzyme-inhibitor complex by means of hydrogen bonds [8][9][10][28][29][30]. Subsequently, various CAI moieties bearing ureido linkers were reported [28][29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our delight, however, there is a large number of mechanistically relevant experiments reported in the literature which address the ability of hCA IX/XII inhibitors to block the growth of hypoxic cancer cells overexpressing the target isozymes [49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67] . Moreover, a certain cohort of studies revealed compounds possessing both favourable hCA inhibitory profile and significant anticancer activity, as exemplified by structures 5-13 ( Figure 2) [49][50][51][52][53][54][55][56][58][59][60][61][64][65][66][67] . In fact, quite a number of single-digit nanomolar hCA IX/XII inhibitors significantly suppressed cancer cell growth.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the drug-like character of some frontrunners makes them intriguing starting points for medicinal chemistry optimisation. Once selected based on their hCA inhibitory profiles, these compounds might be useful indeed in designing antineoplastic drugs either of combinative or single-agent use [49][50][51][52][53]55,56,61,65 .…”
Section: Discussionmentioning
confidence: 99%